Method for completely recovering inorganic fiber reinforced epoxy composite material using boron halide

By using boron halide to react with inorganic fibers and epoxy resins in a one-pot reaction, the problems of high energy consumption and low recovery in the prior art are solved, and efficient recycling of fibers and epoxy resins is achieved.

CN113574101BActive Publication Date: 2025-03-11CLAUSTHAL UNIVERSITY OF TECHNOLOGY +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080020722.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-14
Filing Date
2020-02-27
Publication Date
2025-03-11
Estimated Expiration
2040-02-27

AI Technical Summary

Technical Problem

The prior art has problems of high energy consumption, fiber partial shaping and low recovery when recycling fiber reinforced polymers.

Method used

The one-pot reaction method is used to react inorganic fibers and epoxy resin with boron halide in a solvent to achieve separation and recovery of fibers and polymers.

Benefits of technology

The recovery rate of glass fiber and carbon fiber is achieved to reach about 90%, and the conversion rate of epoxy resin reaches 75-95%, while reducing energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003259014220000041
    Figure BDA0003259014220000041
  • Figure BDA0003259014220000042
    Figure BDA0003259014220000042
  • Figure BDA0003259014220000051
    Figure BDA0003259014220000051
Patent Text Reader

Abstract

The present invention relates to a method for recovering a composite material comprising inorganic fibers and epoxy resin in a one-pot reaction, wherein the method comprises reacting the composite material with a boron halide in a solvent.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to the complete recycling of composite materials comprising inorganic or organic fibers and epoxy resin in a one-pot reaction.

[0002] Fiber-reinforced polymers are composite materials made from a polymer matrix reinforced with fibers. The fibers are typically glass (glass-reinforced plastic, GRP), carbon (carbon-reinforced plastic, CRP), aramid, or basalt. Other fibers, such as paper, wood, or asbestos, are rarely used. [1] The polymer is typically an epoxy, vinyl ester, or polyester thermoset, although phenolic resins are still in use. [2] Fiber-reinforced polymers are increasingly used in the aerospace, automotive, sports, ballistic armor, marine, wind turbine, and construction industries. In the case of carbon fiber reinforced polymers (CRP), the main need for efficient recycling is to recover the intact carbon fibers—the most expensive component of CRP—while in the case of glass fiber epoxy composites (GRP), the main need is to obtain low-molecular compounds for remanufacturing the epoxy resin. Furthermore, in both cases, full recycling implies the use of sustainable technologies.

[0003] The complete recycling of fiber-reinforced polymers includes the recovery of the fibers and the polymer matrix. To date, chemical recycling of fiber-reinforced polymers has utilized high temperatures or strong oxidative conditions in suitable solvents. However, the methods known in the art suffer from high energy consumption, partial shaping of the fibers, and low recovery rates. [3-20]

[0004] Therefore, the object of the present invention is to provide a method for fully recycling inorganic fiber reinforced epoxy resin composite materials that overcomes the disadvantages of the prior art, and in particular, a method for fully recycling inorganic fiber reinforced epoxy resin composite materials that has lower energy consumption, maintains the original fiber structure and quality and results in a high recycling rate.

[21]

[0005] This object is achieved by a process for recovering a composite material comprising inorganic fibers and / or organic fibers, preferably inorganic fibers and an epoxy resin, in a one-pot reaction, wherein the process comprises reacting the composite material with a boron halide in a solvent.

[0006] The present invention provides a chemical process for the complete recycling of various inorganic (e.g., glass (GRP) and carbon (CRP)) fiber reinforced epoxy resin composites with boron halides. The process is a one-pot process and can be considered to include (however, the scope of the present invention need not be limited to this assumption) two steps: the first is the separation of the inorganic fibers from the epoxy resin, and the second is the complete cleavage of the ether bonds in the epoxy polymer, resulting in two low molecular weight structural units.

[0007] The inventors surprisingly found that the method of the present invention can achieve a recovery rate of glass fiber and carbon fiber of about 90%, and a conversion rate of epoxy resin of 75-95%.

[0008] In particular, the present invention allows for complete recycling of fiber-reinforced epoxy resins. In this regard, "complete recycling" refers to a recycling process in which a significant amount of inorganic fibers is recovered as well as a significant amount of epoxy resin. In particular, the term refers to a recycling process in which 90% or more of the inorganic fibers and 75% or more of the epoxy resin can be recovered simultaneously.

[22]

[0009] Without being bound by this theory, it can be assumed that the process of the invention involves three types of bond cleavage in a one-pot reaction: between the cured epoxy resin and the coated fibers, between the crosslinker and the epoxy polymers, and finally their O-C3-units, regioselectively.

[0010] The inorganic fibers may be glass fibers and / or carbon fibers. In this way, particularly good recovery rates have been observed with respect to the inorganic fibers.

[0011] Epoxy resin can be aralkyl ether resin, specifically can be the epoxy resin comprising bisphenol-based monomeric unit and polyol-based monomeric unit.In this way, the particularly good recovery rate about epoxy resin has been achieved.Epoxy resin is a polyether with two terminal epoxy groups in principle.In this regard, aralkyl ether resin is a resin in which an aryl group is connected to an alkyl group through an ether group to form a resin.In this regard, the bisphenol-based monomeric unit is a monomeric unit contained in the epoxy resin, wherein two hydroxyls (prerequisite that these groups are not the end groups of the epoxy resin) contained in the bisphenol molecule participate in the ether bond of the epoxy resin.

[0012] In the case where the epoxy resin contains bisphenol-based monomer units, the bisphenol-based monomer units may be brominated. In this way, the epoxy resin has flame retardant properties.

[0013] Boron halide can be trihaloborane (boron trihalide), organodihaloborane, organooxydihaloborane or a mixture of two or more thereof. In this respect, particularly preferably trihaloborane is selected from BCl and BBr. Further preferably organodihaloborane or organooxydihaloborane have the following formula respectively organic-BHal or organic-OBHal, wherein organic is alkyl, preferably methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl or aryl, preferably phenyl or substituted phenyl (substituent methyl, fluorine, chlorine), and Hal is independently selected from Cl or Br. When using one or more above-mentioned preferred trihaloboranes, the best recovery of inorganic fiber and epoxy resin has been observed.

[0014] The solvent can be selected from hydrocarbons and chlorinated hydrocarbons, including dichloromethane, trichloromethane, 1,2-dichloroethane, trichloroethylene, tetrachloroethylene, hexane, cyclohexane, methylcyclohexane, heptane, octane, toluene, m-xylene, p-xylene, chlorobenzene, o-dichlorobenzene, m-dichlorobenzene, indane, tetralin, cis-decalin, trans-decalin and mixtures of two or more thereof. One or more of the above solvents can be selected to obtain the best recovery rate.

[0015] The reaction can be carried out at a temperature of 0 to 150°C, preferably 15 to 30°C.

[0016] In addition, the reaction can be carried out under a pressure of 1 to 50 bar, preferably under ambient pressure. In this respect, the reaction is most preferably carried out under ambient conditions (room temperature and normal pressure). In this way, the best balance between recovery rate and energy consumption characteristics is achieved.

[0017] The method of the present invention may also include a step of using one or more products obtained by reacting a composite material comprising organic or inorganic fibers and epoxy resin with a boron halide after the reaction. Subsequent uses in this regard (forming further steps) may use a recycled material, such as inorganic fibers, for new applications. The recycled fibers have new product qualities. Similarly, subsequent uses may include remanufacturing one or more chemicals. For example, BCl3 in C of epoxy resin Alk -O cleavage reacts and continuously hydrolyzes to boric acid (H3BO3). Subsequent uses in this regard can be heating to produce B2O3 from H3BO3 and converting this compound again into BCl3 by reaction under appropriate conditions (C+Cl2). Similarly, the monomer units of epoxy resins can be used together or individually to prepare new epoxy resins or for other reactions. The aqueous sodium chloride solution, an industrial by-product of this production, can then be used for electrolysis to obtain caustic soda and chlorine again. The caustic soda can then be used again to couple bisphenols with 1,3-dihalopropanes. In this way, a series of recycling processes ("complete recovery", sustainable method) are created.

[0018] Furthermore, it may be provided that the bisphenol-based monomer units include non-brominated bisphenol-based monomer units and brominated bisphenol-based monomer units, and the method includes a further crystallization step to separate the non-brominated bisphenol-based monomer units and the brominated bisphenol-based monomer units from each other.

[0019] The present application will be described in more detail below by a specific preferred embodiment. However, it should be noted that the preferred embodiment does not necessarily limit the scope of the claims. In addition, it should be noted that one or more aspects of the preferred embodiment, such as specific compounds, specific compound groups referred to by the generic term, reaction conditions, etc., can be combined with the aforementioned generic features individually and in any combination.

[0020] In a preferred embodiment, there is a method for completely recycling different glass and carbon fiber reinforced epoxy resin composites with trihaloborane, organodihaloborane, organooxydihaloborane or mixtures thereof. The bisphenol-based epoxy resin in the starting composite may contain a flame retardant, such as tetrabromobisphenol A (TBBA). The one-pot process comprises two steps: the first is the separation of glass and / or carbon fibers from the epoxy polymer, and the second is the complete cleavage of the polymer into two types of low molecular weight compounds: 1) bisphenols, such as bisphenol A (BPA) or tetrabromobisphenol A (TBBA), and 2) glycerol derivatives, such as 1,3-dichloropropane-2-ol and 1,2,3-tribromopropane. Boron halides, such as boron trichloride and boron tribromide, organohaloboranes, such as phenyldichloroborane or methyldibromoborane, or organooxydihaloboranes, such as phenoxydichloroborane or methoxydibromoborane, can be used either as pure compounds or as solutions in (halogenated) hydrocarbons, such as dichloromethane or heptane. The schematic diagram of the scheme for recycling glass and / or carbon fiber reinforced epoxy resin composites using boron trichloride is shown in Scheme 1.

[0021]

[0022] Scheme 1. Scheme for recycling glass and carbon fiber reinforced epoxy resin composites using boron trichloride.

[0023] 1,3-Dichloropropane-2-ol is a well-known precursor for the synthesis of epichlorohydrin and can itself be converted into bisphenol diglycidyl ether when reacted with bisphenol, an important building block for the manufacture of epoxy resins and other monomers for resins and polymers (Scheme 2).

[23]

[0024]

[0025] Scheme 2. Reuse 1,3-dichloro-2-propanol to prepare epoxy resin.

[0026] Specifically, the more widely used glass and carbon fiber reinforced BPA or BPA-TBBA epoxy composites according to the present invention are completely recovered using trihaloboron, organodihaloborane or organooxydihaloborane to obtain BPA, TBBA, 1,3-dichloropropane-2-ol or 1,2,3-tribromopropane, respectively. The organic products can be easily separated by distillation or recrystallization. The recovery rate of glass fiber and carbon fiber reaches 90%, and the conversion rate of epoxy resin matrix is ​​75-95%. The scheme of recycling glass and carbon fiber reinforced BPA or BPA-TBBA epoxy composites with trihaloborane, organodihaloborane or organooxydihaloborane is shown in Scheme 3.

[0027]

[0028] Scheme 3. Schematic diagram of the scheme for recycling glass and carbon fiber reinforced BPA or BPA-TBBA epoxy composites using trihaloborane, organodihaloborane or organooxydihaloborane.

[0029] In the post-processing process, the treated trihaloborane or organooxydihaloborane is converted into boric acid. Pure boron trichloride (Scheme 4) can be recovered by the BCl3 cycle process (BCl3->H3BO3->B2O3->BCl3) and reused in glass and carbon fiber reinforced epoxy composites. In 2007, about 3.8 million tons of boron trioxide B2O3 were produced worldwide.

[0030]

[0031] Scheme 4. Boron trichloride circulation process flow.

[0032] According to the literature [24-26], by using an organodihaloborane, the consumed boron derivative is converted into a triorganoboroxane after post-treatment, which can also be used to prepare an organodihaloborane by treatment with AlCl3, BCl3, PCl5 or BBr3.

[0033] In the following, the present invention will be described with reference to specific embodiments and accompanying drawings, in which

[0034] From sample 5 Figure 1 Six composite DE sheets are shown 104 ((a), each piece is about 18x10x1.5mm, total weight 3.02g), from DE 104 The glass fiber sheets obtained in (b) were treated with 30 mL of a 1 M BCl3 (3.52 g, 30.00 mmol) solution in DCM at room temperature for 24 h and then at 50–55 °C for 64 h. Four separate fractions VZ-DE-1-1 to VZ-DE-1-4 (c) weighed 370 mg (a mixture of 1,3-dichloropropane-2-ol and bisphenol derivatives), 280 mg (BPA, TBBA and a small amount of impurity 1,3-dichloropropane-2-ol), 40 mg (oligomers and polymers) and 270 mg (oligomers and polymers), respectively.

[0035] From sample 9 Figure 2 Shown is a carbon fiber reinforced epoxy composite from a wind turbine ((a), 18x9x1.5 mm, 493 mg), a portion of the carbon fibers obtained therefrom after treatment with 1 M BCl3 in dry DCM at 60–65 °C for 70 h (b) and a portion of the resulting VZ-CFK-V3 (a mixture of BPA and polymer) (c).

[0036]

[0037]

[0038]

[0039]

[0040]

[0041]

[0042]

[0043]

[0044]

[0045]

[0046]

[0047] Example

[0048] 1) Synthesis of BPA dimethyl ether and cleavage of ether bonds using boron tribromide.

[0049] a) Synthesis of BPA dimethyl ether. To a mixture of BPA (2.28 g, 10.00 mmol) and potassium carbonate (3.48 g, 25.00 mmol) in 25 ml of DMF was added methyl iodide (3.55 g, 25.00 mmol) at 0°C over 10 minutes. The reaction mixture was then stirred at room temperature for 24 hours, poured into 200 ml of cold water, treated with 5 ml of concentrated HCl with stirring and extracted with DCM (4 x 50 mL). The organic layer was washed with water (2 x 100 mL), dried over calcium chloride and concentrated under reduced pressure. After treatment with 10 mL of hexane, the precipitate was filtered off with suction, washed with 5 mL of hexane and dried under reduced pressure. BPA dimethyl ether was obtained as a white solid (yield 2.38 g, 93%).

[0050] pass 1 H-NMR( Figure 3 )and 13 C-NMR( Figure 4 ) characterization.

[0051] b) Cleavage of the ether bond in BPA dimethyl ether with boron tribromide. To a solution of 0.095 mL (250 mg, 1.00 mmol) of BBr3 in 10 mL of dry DCM was added 256 mg (1.00 mmol) of BPA dimethyl ether under stirring at room temperature. After 2 hours, the reaction mixture was poured into 100 mL of ice water and extracted with DCM (4×20 mL). The organic layer was washed with water (2×50 mL), dried with calcium chloride and concentrated under reduced pressure. After treatment with 3 mL of hexane, the precipitate was suction filtered, washed with 1 mL of hexane and dried under reduced pressure. BPA (yield 215 mg, 94%) was obtained as a white solid.

[0052] pass 1 H-NMR( Figure 5 )and 13 C-NMR( Figure 6 ) characterization.

[0053] 2) Synthesis of TBBA ether and cleavage of ether bond using boron tribromide.

[0054]

[0055] TBBA diethyl ether was obtained similarly to BPA dimethyl ether from TBBA (544 mg, 1.00 mmol) and ethyl bromide (2.50 eq.). White solid, yield 570 mg, 95%.

[0056] pass 1 H-NMR( Figure 7 )and 13 C-NMR( Figure 8 ) characterization.

[0057] Similar to the synthesis of BPA from BPA dimethyl ether, the ether bond in TBBA ether (300 mg, 0.50 mmol) was cleaved with boron tribromide. White solid, yield 253 mg, 93%.

[0058] pass 1 H-NMR and 13 C-NMR characterization.

[0059] 3) Recycling of bromine-free glass fiber reinforced epoxy composite G10 using BCl3.

[0060] To a suspension of 3.00 g of G10 powder (about 1.20 g of polymer, 40% content in composite G10) in 10 mL of dry DCM in a 100 mL glass pressure vessel was added 10 mL of 1M BCl3 solution in dry DCM (1.17 g, 10.00 mmol); the reaction mixture was stirred at room temperature for 24 hours and then at 55–60°C for 68 hours. After cooling to room temperature, the reaction mixture was poured into 200 mL of ice water and extracted with DCM (5×50 mL). The organic layer was dried over calcium chloride. The solvent was removed in vacuo to give 775 mg of VZ-G10-4-1 as a dark viscous oil. According to 1 H-NMR spectrum, the product VZ-G10-4-1 is a mixture of 297 mg BPA, 148 mg phenol and 330 mg 1,3-dichloropropane-2-ol (the relationship is 1.00:0.50:1.12, respectively). The residue was washed with a mixture of acetone / methanol 1:1 (3x30 mL), and then washed with ethyl acetate (5x50 mL). After removing the solvent from the combined organic layers under reduced pressure, 30 mL of ether was added to the residue under stirring. The precipitate was filtered off, washed with 5 mL of ether and dried under reduced pressure. The product VZ-G10-4-2 (220 mg) was obtained as a brown solid. According to 1 H-NMR spectrum ( Fig.11 ), the product VZ-G10-4-2 is a mixture of oligomers with a small amount of BPA and phenol. The conversion rate of the organic part of the raw material is 83% (775+220=995 / 1200). The amount of glass fiber after washing with methanol, water, acetone and vacuum drying is 1920 mg.

[0061] pass 1 H-NMR( Fig. 9 )and 13 C-NMR( Fig.10 ) characterization.

[0062] 4) Treating BPA with boron trichloride.

[0063] In sample 3 and some other experiments, we observed the formation of phenol. It is important to examine whether the phenol is formed via a retro-Friedel-Crafts reaction of BPA or is generated directly from the epoxy resin after treatment with BCl3.

[0064] To a suspension of 1.00 g BPA (4.38 mmol) in 10 mL dry DCM in a 100 mL glass pressure vessel was added 30 mL 1M BCl3 (3.52 g, 30.00 mmol) in dry DCM. The reaction mixture was stirred at room temperature for 24 hours and then at 55–60 °C for 40 hours. After cooling to room temperature, TLC test (petroleum ether / ethyl acetate 2:1) showed unreacted BPA, only the formation of phenol was not observed. This confirmed that phenol was formed directly from the epoxy resin.

[0065]

[0066] 5) Recycling DE104 (glass fiber reinforced epoxy composite material with flame retardant tetrabromobisphenol A) with BCl3.

[0067] Six pieces of composite material DE104 (each piece is about 18x10x1.5mm, total weight 3.02g, about 1.20g polymer, content in composite material DE104 is 40%) are placed in 10ml dry DCM in a 100ml glass pressure vessel and 1MBCl3 (1.17g, 10.00mmol) in dry DCM is added. The reaction mixture is stirred at room temperature for 24 hours and then stirred at 50–55°C for 64 hours. Work-up is performed similarly to sample 3, and additional column chromatography is used for fractions 1-3 using a mixture of petroleum ether / ethyl acetate 10:1, and then pure acetone is used for fraction 4. After evaporating the solvent in vacuo, four compounds weighing 370 mg (VZ-DE-1-1, a mixture of 1,3-dichloropropane-2-ol and bisphenol derivatives), 280 mg (VZ-DE-1-2, BPA, TBBA and a small amount of impurity 1,3-dichloropropane-2-ol), 40 mg VZ-DE-1-3 (oligomers and polymers) and 270 mg (VZ-DE-1-4, oligomers and polymers) were obtained. The structures of the obtained compounds were similar to those of the original 1 H- and 13 The C-NMR spectra are the same. The conversion rate of the organic part of the raw material ( Figures 12 to 15 ) is 80% (370+280+40+270=960 / 1200). The amount of glass fiber after washing with methanol, water, acetone and vacuum drying is 1670 mg.

[0068] 6) Recycling of MPM (glass fiber reinforced epoxy composite with flame retardant tetrabromobisphenol A from circuit boards) using BCl3.

[0069] To a suspension of 1.50 g of recycled MPM powder in 5 mL of dry DCM in a 100 mL glass pressure vessel was added 10.7 mL of 1 M BCl3 (1.25 g, 10.70 mmol) in dry DCM. The reaction mixture was stirred at room temperature for 24 hours and then at 55-60°C for 70 hours. Workup was performed similarly to sample 3. After evaporation of the solvent in vacuo, 580 mg of product VZ-MPM-C3 was obtained as a dark viscous oil. 1 H- and 13 C-MR spectrum, product VZ-MPM-C3( Fig.16 and 17 ) is a mixture of BPA, TBBA and 1,3-dichloropropane-2-ol (in a ratio of 1:0.5:2). A small amount of phenol and high molecular weight compounds are also present. The weight of the glass fiber after washing with methanol, water, acetone and vacuum drying is 670 mg.

[0070] 7) Recycling of MPM (glass fiber reinforced epoxy composite with flame retardant tetrabromobisphenol from circuit boards) using BBr3.

[0071] To a suspension of 1.50 g of recycled MPM powder in 20 mL of dry DCM in a 100 mL glass pressure vessel was added 1.02 mL (2.68 g, 10.70 mmol) of BBr3, and the reaction mixture was stirred at room temperature for 1 day and then at 50–55 °C for 1 hour. After cooling to room temperature, the reaction mixture was poured into 200 mL of ice water and extracted with ethyl acetate (3×50 mL). The organic layer was dried over sodium sulfate. The solvent was removed in vacuo to give 590 mg of the product VZ-MPM-BBr-2 as a dark viscous oil. According to 1 H- and 13 C-NMR spectrum, product VZ-MPM-BBr-2( Figures 18 to 20 ) is a mixture of BPA, TBBA and 1,2,3-tribromopropane (relation 1:0.44:1.88, respectively). The weight of the glass fiber after washing with methanol, water, acetone and vacuum drying was 640 mg.

[0072] 8) Recycling of carbon fiber reinforced epoxy composites (CRP from wind turbines, carbon fiber content 70%) with BBr3.

[0073] To a piece of CRP (0.730 g, 20×10×2 mm) in a 25 mL round bottom glass Schlenk flask was added 10 mL of dry DCM and 0.25 mL (0.67 g, 2.67 mmol) of BBr3. The reaction mixture was stirred at room temperature under nitrogen for 4 days. After cooling to -10°C, the reaction mixture was poured into 100 mL of ice water and extracted with ethyl acetate (3×50 mL). The organic layer was dried over sodium sulfate. The solvent was removed in vacuo to give 180 mg of the product VZ-CFK-1 as a dark viscous oil. According to 1 H- and 13 C-NMR spectrum ( Figures 21 to 23 ), the product VZ-CFK-1 is a mixture of BPA, 1,3-dibromopropan-2-ol and a small amount of undefined compound impurities. The weight of the carbon fiber after washing with methanol, water, acetone and vacuum drying is 511 mg.

[0074] 9) Recycling of carbon fiber reinforced epoxy composites (CRP from wind turbines, carbon fiber content 70%) using BCl3.

[0075] To four pieces of CRP (each approximately 25x2x2mm, total weight 0.800g) in a 100mL glass pressure vessel was added 10.7mL of 1M BCl3 (1.25g, 10.70mmol) in dry DCM. The reaction mixture was stirred at room temperature for 24 hours and then at 60-65°C for 70 hours. After cooling to -10°C, the reaction mixture was poured into 200mL of ice water and extracted with ethyl acetate (3×50mL). The organic layer was dried over sodium sulfate. The solvent was removed in vacuo to give 190mg of the product VZ-CFK-V3 as a black solid. According to 1 H-NMR spectrum ( Fig.24 ), the product VZ-CFK-V3 is a mixture of BPA and polymer. The weight of the carbon fiber after washing with methanol, water, acetone and vacuum drying is 515 mg.

[0076] References

[0077] [1] M. Motavalli; C. Czaderski; A. Schumacher; D. Gsell. Textiles, Polymers and Composites for Buildings. 4-Fibre Reinforced Polymer Composite Materials for Building and Construction. Woodhead Publishing Series in Textiles, 2010, 69-128.

[0078] [2]C.E.Bakis;Lawrence C.Bank;V.L.Brown,M.;E.Cosenza;J.F.Davalos;J.J.Lesko;A.Machida;S.H.Rizkalla;and T.C.Triantafillou.Fiber-ReinforcedPolymer Composites for Construction,J.Composites for Construction,2002,6(2),doi.org / 10.1061 / (ASCE)1090-0268(2002)6:2(73)。

[0079] [3]Liang,B.;Qin,B.;Pastine,S.;Li,X.Reinforced Composite and Methodfor Recycling the Same,US 20140221510 A1,2014。

[0080] [4]Adam,G.A.Recycling Carbon Fibers from Epoxy Using SolventCracking.US 8920932,2014。

[0081] [5]Asmatulu,E.;Twomey,J.;Overcash,M.Recycling of Fiber-ReinforcedComposites and Direct Structural Composite Recycling Concept.J.CompositeMaterials,2014,48(5),593-608。

[0082] [6]Taynton P.;Ni H.;Zhu C.;Loob S.;Jin Y.;Zhang W.;Qi H.J.RepairableWoven Carbon Fiber Composites with Full Recyclability Enabled by MalleablePolyimine Networks.Advanced materials(Deerfield Beach,Fla.),2016,28(15),2904-9。

[0083] [7]Kaneko,M.;Usami,K.;Ishimoto,T.Prepregs and Fiber-ReinforcedComposites Therefrom.Jpn.Kokai Tokkyo Koho,2010,JP 2010241845。

[0084] [8]Y.Wang,X.Cui,H.Ge,Y.Yang,Y.Wang,C.Zhang,J.Li,T.Deng,Z.Qin,X.Hou.Chemical Recycling of Carbon Fiber Reinforced Epoxy Resin Compositesvia Selective Cleavage of the Carbon-Nitrogen Bond.ACS SustainableChem.Eng.2015,3,3332-3337。

[0085] [9]M.Das,R.Chacko,S.Varughese.An Efficient Method of Recycling ofCFRP Waste Using Peracetic Acid.ACS Sustainable Chem.Eng.2018,6(2),1564–1571,DOI:10.1021 / acssuschemeng.7b01456。

[0086]

[10] K.Yu,Q.Shi,M.L.Dunn,T.Wang,H.J.Qi.Carbon Fiber ReinforcedThermoset Composite with Near 100%Recyclability.Adv.Funct.Mater.2016,26,6098–6106。

[0087]

[11] W.Guo,S.Bai,Y.Ye and L.Zhu.Recycling carbon fiber-reinforcedpolymers by pyrolysis and reused to prepare short-cut fiber C / Ccomposite.Journal of Reinforced Plastics&Composites.2019 0(0)I-9。

[0088]

[12] K.Kim,J.Jeong,K.An,B.Kim.A Low Energy Recycling Technique ofCarbon Fibers-Reinforced Epoxy Matrix Composites.Ind.Eng.Chem.Res.2019,58,618-624。

[0089]

[13] M.Limburg,J. P.Quicker.Thermal treatment of carbonfiber reinforced polymers(Part 1:Recycling).Waste Management&Research 2019,Vol.37(1)Supplement 73-82。

[0090]

[14] Y.Liu,M.Farnsworth,A.Tiwari.A review of optimisation techniquesused in the composite recycling area:State-of-the-art and steps towards aresearch agenda.Journal of Cleaner Production 140(2017)1775-1781。

[0091]

[15] M.Overcash,J.Twomey,E.Asmatulu,E.Vozzola,E.Griffing.Thermosetcomposite recycling–Driving forces,development,and evolution of newopportunities.Journal of Composite Materials.2018,Vol.52(8)1033-1043。

[0092]

[16] J. S.Baz,J.Schwingel,G.Gresser,P.Middendorf,C.Bonten.Recycling of composites–A new approach minimizes downgrading.AIPConference Proceedings 2055,060009(2019)。

[0093]

[17] WO2017 / 106243 A1。

[0094]

[18] K.Pender and L.Yang.Investigation of Catalyzed Thermal Recyclingfor Glass Fiber-Reinforced Epoxy Using Fluidized Bed Process.PolymerComposites 2019 1-10。

[0095]

[19] WO2017 / 175100 A1。

[0096]

[20] WO2018 / 206788 A1。

[0097]

[21] P. J.Pfrommer,S.Enthaler.Recycling Concept for End-of-LifeSilicones:Boron Trifluoride Diethyl Etherate as Depolymerization Reagent toProduce Difluorodimethylsilane as Useful Commodity.ACS SustainableChem.Eng.2015,3,163-169。

[0098]

[22] N.M.R.Chipa;V.P.Jatakiya;P.A.Gediya;S.M.Patel,and D.J.Sen.GreenChemistry:an Unique Relationship Between Waste and Recycling,Int.J.Adv.Pharm.Res.,2013,4(7),2000–2008。

[0099]

[23] Li,F.Xia,J.;Xiong,Y.;Tang,X.;Cheng,Y.Process for Preparation ofEpichlorohydrin and Dichloropropanol Intermediates,Faming Zhuanli Shenqing,101195607,2008。

[0100]

[24] Al-Juaid, SS; Eaborn, C.; El-Kheli, MNA; Hitchcock, PB; Lickiss, PD; Molla, ME; Smith, JD; Complex[(MeOH)2Li(μ-OMe)2B(OMe)2]. J. Chem. Soc., Dalton Trans.: Inorganic Chem., 1989, 3, 447-52.

[0101]

[25] Bayo-Bangoura, M.; Bayo, K.; Mossoyan-Deneux, M.

[0102]

[26] Ishihara, K.; Kondo, S.; Yamamoto, H. Scope and Limitations of ChiralB-[3,5-Bis(trifluoromethyl)phenyl]oxazaborolidine Catalyst for Use in the Mukaiyama Aldol Reaction. J. Org. Chem., 2000, 65(26), 9125-9128.

[0103] The features disclosed in the preceding description and in the dependent claims can in various forms realize the aspects of the disclosure set out in the independent claims both individually and in any combination thereof.

[0104] Name and description of materials used

[0105]

Claims

1. A method for completely recovering a composite material comprising an inorganic fiber and an epoxy resin in a one-pot reaction, wherein the method comprises reacting the composite material with a boron halide in a solvent, wherein the epoxy resin comprises an alkyl aryl ether resin portion, wherein the boron halide is a boron trihalide selected from BCl3 and BBr3, and The solvent is a hydrocarbon, a halogenated hydrocarbon or a mixture of two or more thereof.

2. The method according to claim 1, wherein the inorganic fibers are glass fibers and / or carbon fibers. 3 . The method according to claim 1 , wherein the epoxy resin comprises a bisphenol-based monomer unit and a polyol-based monomer unit.

4. The method according to claim 3, wherein the bisphenol-based monomer units are brominated.

5. The method according to claim 1, wherein the reaction is carried out at a temperature of 0 to 150°C.

6. The method of claim 3, wherein the bisphenol-based monomer units include non-brominated bisphenol-based monomer units and brominated bisphenol-based monomer units, and the method includes a further step of crystallizing to separate the non-brominated bisphenol-based monomers and the brominated bisphenol-based monomers from each other.

7. The method according to claim 1, further comprising the step of using one or more products obtained by reacting a composite material comprising an inorganic fiber and an epoxy resin with a boron halide after the reaction.

Citation Information

Patent Citations

  • Prepreg and fiber-reinforced composite material obtained by curing the same

    JP2010241845A

  • Recycling carbon fiber based materials

    WO2017106243A1

  • Recycling of polymer matrix composite

    WO2017175100A1

  • Method for recycling fiber-reinforced composite materials

    WO2018206788A1

  • Application of heteropoly acid and lewis acid as catalyst to degradation of thermosetting resin

    CN107365429A